Mediatizing Tradition: The Role of Tengku Dayah in Shaping Digital Da‘wah in Contemporary Aceh - Samsuar, Samsuar; Siregar, Zakaria; Bilardo, Topan; Rizal, Syamsul (MUHARRIK: Jurnal Dakwah dan Sosial, 2025)
The development of digital media has changed the global communication landscape, including in the religious realm. Social media has become a powerful tool to spread teachings and influence people's views. However, this phenomenon challenges traditional religious authorities in reaching people increasingly exposed to digitalization. This study examines the transformation of Tengku Dayah, a traditional Acehnese scholar, who switched from physical da'wah to digital platforms, especially social media, in response to the demands of the digital era. Using a qualitative approach and case study methods, this study shows a paradigm change in the acceptance of social media as a da'wah tool while maintaining spiritual integrity, changes in the da'wah space also change the way and pattern of communication to be more relaxed and interactive according to the choice of platforms such as TikTok and YouTube. This research offers practical implications that support the transformation of Tengku Dayah's digital da'wah in the face of the constraints of the digital divide, with targeted digital literacy training programs and student support also being an effective solution, different from previous digital da'wah research that emphasized adoption trends, this study uniquely dissects the internal ethical dilemmas and adaptation strategies of tengku, which enriches the understanding of the sustainable relevance of tengku. Based on the socio-religious context of Aceh, these insights advance the study of digital religion and offer practical implications for traditional Islamic authorities.